Recent development of efficient A-D-A type fused-ring electron acceptors for organic solar. (1st November 2018) - Liu, Zhitian; Zhang, Xiaolu; Li, Pengcheng; Gao, Xiang
Abstract: The development of acceptor-donor-acceptor (A-D-A) type fused-ring electron acceptors boosted the energy conversion efficiency of organic solar cells. Certified record power conversion efficiencies of single junction organic solar cells have exceeded 14%. In this paper, we briefly reviewed the development of A-D-A type fused-ring electron acceptors which were reported since 2014. The planarity of the central donor moieties, the effects of bulky side-chain and the end-group modification were highlighted.